Identifikasi Potensi Desa Wisata Kerta Payangan, Kabupaten Gianyar, Bali - Wiguna, Putu Aditya Dharma Arya; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2019)
Tourist village of Kerta is one of village in Gianyar Regency that the tourist village which has tourism potential that range from cultural, natural, artificial and can be developed as a tourist destination or attraction for tourists. The purposes of this study is to know the identification of the potential of tourist village of Kerta. The location of this research in the tourist village of Kerta, which has the location integrated with agriculture and tourism. The research in the tourist village of Kerta was conducted to discover the potential of the village (cultural, natural, and artificial potential of the tourist village). This research uses techniques of observation, interview, and documentation. The data analysist technique used is descriptive qualitative analysist. The purposive sampling technique using informants and use key informant. The results of this reserch shows that there are a variety of potential tourist villages grouped into three parts, among others, the natural potential (indigenous forests, bamboo forests, paddy fields, citrus plantations and, organic plantations), cultural potential (site sarcophagus, Bali Aga traditions, and Alas Angker Temple), and artificial potential (Puncak Sari campground, tracking and cycling trails, and Munduk Asri). Also accordingly with the potential that is owned by the village and developed on an ongoing basis to achieve positive benefits for the life of the local community. Keywords: Identification, Tourist Village, Kerta Village